Detection of Schistosoma mansoni eggs in feces through their interaction with paramagnetic beads in a magnetic field. - Candida Fagundes Teixeira; Erli Neuhauss; Renata Ben; Juliano Romanzini; Carlos Graeff-Teixeira (Public Library of Science (PLoS), 2007)
BACKGROUND: Diagnosis of intestinal schistosomiasis in low endemic areas is a problem because often control measures have reduced egg burdens in feces to below the detection limits of classical coproparasitological methods. Evaluation of molecular methods is hindered by the absence of an established standard with maximum sensitivity and specificity. One strategy to optimize method performance, where eggs are rare events, is to examine large amounts of feces. A novel diagnostic method for isolation of Schistosoma mansoni eggs in feces, and an initial evaluation of its performance is reported here. METHODOLOGY/PRINCIPAL FINDINGS: Known amounts of S. mansoni eggs were seeded into 30 g of normal human feces and subjected to a sequence of spontaneous sedimentation, sieving, Ritchie method, incubation and isolation through interaction with paramagnetic beads. Preliminary tests demonstrated the efficacy of lectins as ligands, but they also indicated that the paramagnetic beads alone were sufficient to isolate the eggs under a magnetic field through an unknown mechanism. Eggs were identified by microscopic inspection, with a sensitivity of 100% at 1.3 eggs per gram of feces (epg). Sensitivity gradually decreased to 25% at a concentration of 0.1 epg. In a preliminary application of the new method to the investigation of a recently established focus in southern Brazil, approximately 3 times more eggs were detected than with the thick-smear Kato-Katz method. CONCLUSIONS/SIGNIFICANCE: The novel S. mansoni detection method may significantly improve diagnosis of infections with low burdens in areas of recent introduction of the parasite, areas under successful control of transmission, or in infected travelers. It may also improve the evaluation of new treatments and vaccines.